STUDI DESKRIPTIF PENERAPAN PENDIDIKAN KARAKTER ANAK TUNAGRAHITA SEDANG DI SEKOLAH DASAR LUAR BIASA - Putra, Galih Dwiana (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
Character education is not only applied in public schools, but also for special schools with students who have special needs. This study aims to find out: (1) Application of honest character education discipline and responsibility for children with mental retardation in Banyumas Elementary School (2) Obstacles in the implementation of character education for mentally retarded children in SDLB Banyumas (3) Solutions to overcome obstacles in the application of education the character of mentally retarded children is at the Banyumas Primary School. This research was conducted at the Banyumas Elementary School. This research uses a descriptive method with data collection techniques through interviews, observation, and documentation study. Participants in the study were Principals, Teachers, Parents of moderate mentally retarded children, and Students with a classification of moderate retardation children. The results of the study are as follows: 1) The application of character education at the Banyumas Elementary School has been going well. This can be seen from the strategies and media of learning carried out by the teacher in applying character values. 2) Obstacles in the application of character education in Banyumas Elementary School are from aspects of physical characteristics, psychological characteristics, social characteristics, and aspects of parents or family. 3) Solutions to overcome obstacles in the application of character education, among others: the use of appropriate learning strategies supported by the learning media used, therapeutic classes, working with psychologists to determine children’s abilities, and also the direction or understanding of the school to parents of students. Based on the results of the study, it can be concluded that the application of character education at the Banyumas Elementary School has been going well. It can be assessed from the success of the school in implementing character education from the stages of socialization, planning, implementation, evaluation, development, and learning strategies used by the teacher. To overcome the obstacles, the solution that the school takes is to work together with a psychologist and also hold a guardian meeting with the parents of students.